The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1086/653713
|View full text |Cite
|
Sign up to set email alerts
|

Training and Innovation

Abstract: Research analyzing the importance of human capital for innovation usually focuses on secondary and tertiary education. This paper takes a different perspective by focusing on in-firm training. We argue that continuous training guarantees access to leading-edge knowledge and thus increases a firm's propensity to innovate. Using German establishment-level data, we show a strong association between lagged continuous training and innovation. Applying instrumental variable methods, we cautiously argue that the asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 34 publications
4
72
0
3
Order By: Relevance
“…Credit constraint = Constrained (1) and (2), Rejected in columns (3) and (4), and Constrained in columns (5) and (6). Access to finance problematic is the answer to the question: "How problematic is access to finance for the operation and growth of your business" (1 = no obstacle, 2 = minor obstacle, 3 = moderate obstacle, 4 = major obstacle).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Credit constraint = Constrained (1) and (2), Rejected in columns (3) and (4), and Constrained in columns (5) and (6). Access to finance problematic is the answer to the question: "How problematic is access to finance for the operation and growth of your business" (1 = no obstacle, 2 = minor obstacle, 3 = moderate obstacle, 4 = major obstacle).…”
Section: Resultsmentioning
confidence: 99%
“…When I proxy …rm credit constraints with the variable Constrained, the e¤ect of credit constraints on training survives once again, and is again signi…cant at the 10% (column (6) in both Panel A and Panel B). The …rst-stage suggests that a higher concentration of bank branches is again associated with signi…cantly higher access to …nance (column (5)).…”
Section: Instrumental Variable Regressions In the Cross-sectionmentioning
confidence: 92%
“…Well-trained workers are more likely to understand the complexities of a firm's production processes, and therefore identify and implement technological improvements, especially incremental innovations to improve existing products and processes. A study of German establishments documented this connection and found a clear relationship between the extent of in-company training and subsequent innovation [11].…”
Section: Estimating the Post-training Benefits Of Apprenticeshipsmentioning
confidence: 90%
“…In this sense, training is critical in order to leverage the human capital of firms to make an efficient contribution to the firms' efficacy and performance (Arthur, 1994;Bauernschuster et al, 2009;Chen and Huang, 2009;Delaney and Huselid, 1996;Richard and Johnson, 2001;Shipton et al, 2005;Tharenou et al, 2007;Van Eerde et al, 2008). Thus, it is not surprising that more innovative firms pay more attention to the training of their employees (Baldwin and Johnson, 1998;Freel, 2005).…”
Section: Theoretical Framework and Research Hypothesismentioning
confidence: 99%